Effect of Process Annealing Temperature on Some Tensile Properties and Microstructure of Cold Rolled 1010 Steel (Journal of Academic Research, 2022)
This paper aims to investigate the effect of temperature of processannealing heat treatment on some tensile properties and microstructureof cold-rolled 1010 steel. The cold-rolled sheet was cut into thestandard tensile test specimens and then the samples were annealed at300, 400, 500, 550, 600, and 650oC. Tensile and microscopic tests wereconducted on the samples. Process annealing temperatures had asignificant effect on properties and microstructure. Yield and Ultimatetensile strengths decreased massively from 638 and 662 MPa of thecold rolled steel to 169 and 309 MPa respectively of the treatedsamples at 650oC. On the other hand, percent elongation improvednoticeably from 2 to 35 percent. The microstructure showed aformation of a new set of free-strain grains, that is, the recrystallizationtemperature, starting at 600oC and finishing at 650oC. This range wasof the transition from brittle to ductile fracture. The dominantmicrostructure was ferrite and pearlite, with elongated grains before600oC and recrystallized grains at 600oC and above.